Hematological values of creole goats in two reproductive physiological states (Scientia Agropecuaria, 2013)
The present study aimed to determine the hematological values of creole goats in two reproductive physiological states in the Agricultural Experimental Center – Virú of the National University of Trujillo. It was performed the blood analysis of 24 goats of 3-4 years old, was made for this, two samplings, with one month of difference between the two. Were evaluated the erythrocyte series, leukocyte and corpuscular constants. For data analysis was used descriptive statistics and Student t test. The results of the first sampling of blood for pregnant and non-pregnant goats were showing significant statistically differences (p < 0.05) in Ht, Hb and RBCs. The results of the second sampling no showed significant statistically differences (p > 0.05); however, was there appearance of tables anemic in all goats. It concludes that hematological values of native goats vary according to their reproductive physiological states.
Keywords: Creole goats; reproductive physiological states; pregnant; non-pregnant; hematologic values.